2015
DOI: 10.1590/s0100-204x2015000500008
|View full text |Cite
|
Sign up to set email alerts
|

Mineralização e efeitos de biocarvão de cama de frangosobre a capacidade de troca catiônica do solo

Abstract: O objetivo deste trabalho foi caracterizar o processo de mineralização do C em amostras de cama de frango e de seu respectivo biocarvão, além de determinar a capacidade de troca catiônica (CTC) e as taxas de mineralização do C nos solos tratados com cama de frango e biocarvão. A mineralização do C foi avaliada em experimento com quantificação do C-CO2 liberado a partir de incubação (64 dias) de misturas de solo com cama de frango e de solo com biocarvão, em doses equivalentes a 0, 1.000, 2.000, 4.000 e 8.000 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
1
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
(36 reference statements)
7
14
1
8
Order By: Relevance
“…A 47% increase in OM content was observed at the 160 t ha -1 dose compared to the controls, albeit within the reference range (Table 1). Similar results were reported by Lima et al (2007), Silva et al (2012) and Andrade et al (2015) when using poultry litter as an organic fertilizer. This indicates improvement of soil quality, since loam texture soils such as the one evaluated herein display increased water retention, due to organic matter increases, in addition to increasing nutrient availability to plant root systems (Kiehl, 1997).…”
Section: ------------------------------------------------------------supporting
confidence: 87%
See 1 more Smart Citation
“…A 47% increase in OM content was observed at the 160 t ha -1 dose compared to the controls, albeit within the reference range (Table 1). Similar results were reported by Lima et al (2007), Silva et al (2012) and Andrade et al (2015) when using poultry litter as an organic fertilizer. This indicates improvement of soil quality, since loam texture soils such as the one evaluated herein display increased water retention, due to organic matter increases, in addition to increasing nutrient availability to plant root systems (Kiehl, 1997).…”
Section: ------------------------------------------------------------supporting
confidence: 87%
“…Soil pH values were directly influenced by the poultry litter doses, where the highest value was 7.45 at 136 t PL ha -1 (Figure 3), with pH increase over 13 % comparing the control and the highest tested poultry litter dose. Santos et al (2004) and Andrade et al (2015) observed a rise in soil pH with poultry litter applications, justified by the presence of calcium carbonate and calcium oxide (Table 2) from the poultry litter disinfection treatments carried out between bird lots. Doses higher than 20 t PL ha -1 altered pH values to above the reference values for agriculture, which ranges from 5.5 to 6.3 t PL ha -1 (Table 1).…”
Section: Evaluation Of Soil Chemical Attributesmentioning
confidence: 96%
“…El contenido de nitrógeno obtenido fue mayor para la pollinaza (2,48 %) que para la gallinaza (1,90 %). Otro autor 4 reportó valores cercanos (2,3 %) para la pollinaza, sin embargo el autor 14 reportó para la gallinaza 3,24 %, siendo este valor casi el doble del valor obtenido. Así, la relación carbono y nitrógeno (C/N) obtenido está entre (9,27-9,89) para la gallinaza y pollinaza, respectivamente, valor muy cercano al encontrado por otros autores 4,13 para la pollinaza 9,7 y 9,79, respectivamente, sin embargo, otro autor 4 reporta un valor un poco alto para la gallinaza (12,02), así 14 , reporta una pequeña variación (9,79), se observa sin embargo que la mezcla de estos dieron menores resultados (6,75).…”
Section: Resultados Y Discusiónunclassified
“…3A). The potential acidity decreased by raising chicken manure doses, probably due to the increase of electric charges in the soil by the addition of organic matter [24].…”
Section: Resultsmentioning
confidence: 99%